Utilizing Administrative Data to Focus Quality Improvement Efforts for Opioid Prescribing in an Integrated Health System. Issue 1 (10th May 2018) - Ramar, Priya; Roellinger, Daniel L.; Ebbert, Jon O.; Lovely, Jenna K.; Philpot, Lindsey M.
This case study describes the use of multiple administrative data sources within a large, integrated health care delivery system to understand opioid prescribing patterns across practice settings. We describe the information needed to understand prescribing patterns and target interventions, the process for identifying relevant institutional data sources that could be linked to provide information on the settings for prescriptions, and the lessons learned in developing, testing, and implementing an algorithm to link the data sources in a useful manner.